Analisis Metode SAW dan WP dalam Pemilihan Costumer Service Berdasarkan Pembobotan ROC - Agus Iskandar (JURIKOM (Jurnal Riset Komputer), 2023)
Customer Service is a job whose main task is to be a direct liaison between the company and its customers. Every company needs customer service in order to launch its business journey. Therefore, customer service has an important role in improving the sales quality of the company, whether selling goods, services or whatever business the company is running. In choosing a quality customer service it will be very difficult if it is done manually because it can result in incorrect decisions because the choices that are selected manually are not guaranteed. To overcome these problems, a computerized system is needed to select service customers. A good system used is a decision support system. A decision support system is a system that has been used by many people in making elections or making decisions that have a large number of alternatives. In this study the method used is the SAW method and the WP method. The weighting method used is the ROC method. These three methods are used because this method is a method that can be used easily and the results obtained have accurate and reliable results. Based on the results of calculations using the SAW method, a value of 0.9843 is obtained as an alternative to A2 on behalf of Verawati as the best alternative. While calculations using the WP method obtained a value of 0.2473 as an alternative to A2 on behalf of Verawati as the best alternative